Biophilic Philosophy of Josef Šmajs - Lípa, Jan; Rozenský, Ladislav; Ondrušák, Petr; Vrba, Zdeněk; Dolista, Josef (Studia Ecologiae et Bioethicae, 2022)
In the field of ecoethics, in addition to names such as Kohák, Vavroušek, Keller, and Librová, we are increasingly encountering the name of a Czech philosopher, Professor Josef Šmajs. In his works, Professor Šmajs presents an entirely new, original, and comprehensive view of human life on Earth and its ethics. His concept combines the humanities and natural sciences into a single organic whole. Šmajs declares: “We are the products of a magnificent natural evolution, but we are proud only of our cultural creativity. We think – and we teach it in schools – that we complete humanity with human culture and humanize it. However, the truth is different. Nature is original, self-sufficient, and perfect; we cannot complete or humanize it.” He further claims that “If we want to survive on Earth, we must wisely give way to nature wisely in time. The epoch of the symbiosis of culture and nature is still ahead of us.” His philosophy, which can be called biophilic, interprets the current form of the ecological crisis and its causes and provides a clear, realistic guide to saving humanity and life on earth in ethical manner.